The Effect Contextual Teaching-Learning Approach on Improving Students’ Mathematical Reasoning Ability and Self Concept - Toni Alamsyah; Utari Sumarmo; Asep Kustiana ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2020)
The goal of this research is to examine  the role of contextual teaching-learning  approach (CTLA) toward  students’ mathematical reasoning ability (MRA) and self concept in mathematics (MSC). The research involves 66 eighth grade students, a MRA  test,  a MSC scale. Findings of this research were:  students getting CTLA reached MRA at better grade than the grade of students who get SA learning, even if those grades were at low level. However, there was no difference grades on students’ MSC in both teaching approaches, and those grades were at fairly good level. Students in both teaching approaches encountered difficulties in solving MRA tasks such as on analogical reasoning about position of two lines,  solving tangent equation on a curve problem, and writing down the formula involved in a calculation.  Beside that, there was association between MRA and MSC, and students performed active learning during CTLA lessons.Keyword: contextual teaching-learning, mathematical reasoning, mathematcal self concept.